United States Clergy Religious Values and Relationships to End-of-Life Discussions and Care - Balboni, Michael J. (J Pain Symptom Manage, 2017)
CONTEXT: While clergy interact with approximately half of U.S. patients facing end-of-life medical decisions, little is known about clergy-congregant interactions or clergy influence on end-of-life decisions. OBJECTIVE: To conduct a nationally representative survey of clergy beliefs and practices. METHODS: A mailed survey to a nationally representative sample of clergy completed in March 2015 with 1005 of 1665 responding (60% response rate). The primary predictor variable was clergy religious values about end-of-life medical decisions, which measured belief in miracles, the sanctity of life, trust in divine control, and redemptive suffering. Outcome variables included clergy-congregant end-of-life medical conversations and congregant receipt of hospice and ICU care in the final week of life. RESULTS: Most U.S. clergy are Christian (98%), and affirm religious values despite a congregant’s terminal diagnosis. Endorsement included God performing a miracle (86%), pursuing treatment because of the sanctity of life (54%), postponement of medical decisions because God is in control (28%), and enduring painful treatment because of redemptive suffering (27%). Life-prolonging religious values in end-of-life medical decisions were associated with fewer clergy-congregant conversations about considering hospice (adjusted odds ratio [AOR], 0.58; 95% CI, 0.42 to 0.80), p<0.0001), stopping treatment (AOR 0.58, 95% CI: 0.41, 0.84, p=0.003), and forgoing future treatment (AOR 0.50, 95% CI: 0.36, 0.71, p<0.001), but not associated with congregant receipt of hospice or ICU care. Clergy with lower medical knowledge were less likely to have certain end-of-life conversations. The absence of a clergy-congregant hospice discussion was associated with less hospice (AOR 0.45; 95% CI, 0.29, 0.66, p<0.001) and more ICU care (AOR 1.67; 95% CI, 1.14,2.50, p<.01) in the final week of life. CONCLUSION: American clergy hold religious values concerning end-of-life medical decisions, which appear to decrease end-of-life discussions. Clergy end-of-life education may enable better quality end-of-life care for religious patients.